Webinar Summary Report: Targeting Tools 2.0: Targeting and out-scaling interventions in agricultural systems – Zambia - Mutua, John Y. (2021)
The second webinar to raise awareness on Targeting Tools 2.0 was held on the 21st April 2021 through Microsoft Teams. Project team members from the GIZ funded project “Towards climate-resilient dairy production in Southern Zambia” participated. Scientists from the Alliance of Bioversity International and CIAT guided participants through the tool’s capabilities and how to leverage the features to assess gaps and opportunities for improving and expanding the choice of intervention options while designing programmes for sustainable agricultural intensification at a range of scales. 21 participants from drawn from academia, NGO and research institutions participated in the discussions following the presentations.